Looking south : Australia's Antarctic agenda - Jabour, J; Hemmings, AD; Kriwoken, L (2007)
Australia's Antarctic Policy Options provided a benchmark by which to measure the tenor of Australia's contemporary Antarctic agenda and as such has been of great assistance to us individually and collectively. Consequently 20 years on we thought it timely to explore how the issues identified in that volume might have developed and whether any significant new issues had emerged. Our focus, as with Harris, was on Antarctica from an essentially Australian perspective. The core project group was drawn from the Institute of Antarctic and Southern Ocean Studies (IASOS) and the Policy Program of the Antarctic Climate and Ecosystems Cooperative Research Centre (ACE CRe, University of Tasmania), the Centre for International and Global Law (University of Sydney Law School), the Australian National University College of Law, and the University of New South Wales (School of Social Sciences and International Studies). Following substantial exchanges and sub-group discussions, the group as a whole came together in two workshops, the first in Sydney in November 2004 and the second in Hobart in July 2005, where we were fortunate to also be able to draw upon expertise from the Australian Antarctic Division (AAD). At the workshops various topics were presented and critiqued, inspiring more free ranging discussion across issues as they emerged. Thereafter authors prepared the chapters you now see in this volume. The project did not aim to create a unitary interpretation of issues or Australia's engagement with the Antarctic. Nor did we aspire to a systematic coverage of all current Antarctic issues, although we believe that the most significant are in fact addressed. Where linkages between chapters are evident, some cross-referencing has been done, but the chapters are largely stand-alone. Because the authors represent a range of disciplines, with a corresponding wide range of discipline-specific styles and protocols, we have, with the authors' agreement and cooperation, edited the chapters into a constant house style. We hope ...